Rare presentation of parotid duct rhinosporidiosis: A case report - Dr N. Puneeta; Dr T. Santosh; Dr Pravin Gaikwad (Elsevier, 2018)
Rhinosporidiosis is caused by Rhinosporidium seeberi, a protist of class Mesomycetozoea, which comprises mostly uncultivable aquatic microbes at the animal-fungal boundary. It chiefly affects the mucous membranes of the nose, oropharynx and nasopharynx. It also involves many rare sites and may become disseminated to occur in a generalized form. Soil and water act as a reservoir for the organism. Rhinosporidiosis of the parotid duct is rare and there are very few reported cases in the Indian literature and world-wide. Our case report of a 20-year-old female presenting with facial swelling, the duct cyst was excised and submitted for histopathological examination which confirmed the diagnosis of rhinosporidiosis due to the presence of sporangia and endospores in the wall of the cyst. Keywords: Parotid duct, Rhinosporidiosis, Granulomatous disease, Wet mount